Functional Comparison of Interferon‐α Subtypes Reveals Potent Hepatitis B Virus Suppression by a Concerted Action of Interferon‐α and Interferon‐γ Signaling. Issue 2 (15th February 2021) - Chen, Jieliang; Li, Yaming; Lai, Fritz; Wang, Yang; Sutter, Kathrin; Dittmer, Ulf; Ye, Jianyu; Zai, Wenjing; Liu, Min; Shen, Fang; Wu, Min; Hu, Kongying; et al.
Abstract : Background and Aims: Interferon (IFN)‐α, composed of numerous subtypes, plays a crucial role in immune defense. As the most studied subtype, IFN‐α2 has been used for treating chronic hepatitis B virus (HBV) infection, with advantages of finite treatment duration and sustained virologic response, but its efficacy remains relatively low. This study aimed to screen for IFN‐α subtypes with the highest anti‐HBV potency and to characterize mechanisms of IFN‐α–mediated HBV restriction. Approach and Results: Using cell culture–based HBV infection systems and a human‐liver chimeric mouse model, IFN‐α subtype–mediated antiviral response and signaling activation were comprehensively analyzed. IFN‐α14 was identified as the most effective subtype in suppression of HBV covalently closed circular DNA transcription and HBV e antigen/HBV surface antigen production, with median inhibitory concentration values approximately 100‐fold lower than those of the conventional IFN‐α2. IFN‐α14 alone elicited IFN‐α and IFN‐γ signaling crosstalk in a manner similar to the combined use of IFN‐α2 and IFN‐γ, inducing multiple potent antiviral effectors, which synergistically restricted HBV replication. Guanylate binding protein 5, one of the most differentially expressed genes between IFN‐α14–treated and IFN‐α2–treated liver cells, was identified as an HBV restriction factor. A strong IFN‐α–IFN‐α receptor subunit 1 interaction determines the anti‐HBV activity of IFN‐α. The in vivo anti‐HBV activity of IFN‐α14 and treatment‐related transcriptional patterns were further confirmed, and few adverse effects were observed. Conclusions: A concerted IFN‐α and IFN‐γ response in liver, which could be efficiently elicited by IFN‐α subtype 14, is associated with potent HBV suppression. These data deepen the understanding of the divergent activities of IFN‐α subtypes and the mechanism underlying the synergism between IFN‐α and IFN‐γ signaling, with implications for improved IFN therapy and HBV curative strategies.